To Rotate or to Link? The Connection Between the Red Sea and Gulf of Aden Rifts in Central Afar - Ameha Muluneh; Sascha Brune; Carolina Pagli; Alessandro La Rosa; Derek Keir; Derek Neuharth; Giacomo Corti (Geophysical Research Letters)
Abstract Central Afar is shaped by the interaction between the Red Sea (RS) and Gulf of Aden (GoA) rifts. While there have been several studies conducted in the region, we know surprisingly little about the mechanism of connection between these two rift branches. Here we use high‐resolution 3D lithospheric scale geodynamic modeling to capture the evolution of linkage between the RS and GoA rifts in central Afar. Our results demonstrate that the two rifts initially overlap and interact across a broad zone of faulting and vertical axis block rotation. However, through time, rift overlap is abandoned in favor of direct linkage which generates a series of localized en‐echelon basins. The present‐day direct linkage between the two rifts is supported by geodetic observations. Our study reconciles previously proposed models for the RS and GoA rift connection by considering spatial and temporal evolution of the rifts.